Estudo dos efeitos das pontes, rugosidade e declividade longitudinal no escoamento em canal artificial urbano aplicando modelagem computacional - Cavalcante, Francisco Guedes (2017)
The dissertation presents a study on the effects that roughness, in the slope and the presence of the bridges, exert on the flow in the canal artificial urban Rio Granjeiro, Crato, Ceará, Brazil. In carrying out this work The HEC-RAS software was used, which presents the ability to simulate gradually varied, abruptly varied flow and flow through sections with bridges. To obtain the results, we tried to discriminate the effects separated from each of the singularities. For the roughness, three simulations, representing three possible scenarios for the roughness of the slopes and the bottom of the channel. In order to analyze the effects of the change in slope, the flow of two stretches in the canal, a stretch of greater slope with another one of smaller declivity. And the effects of the bridges were analyzed through two simulations, in which the characteristics of the flow in the channel with the bridges inserted and without the insertion of the bridges. The results showed that the effects of increased roughness, significant for the formation of the hydraulic rebound and added to the declivity, lead to regime change. The adverse effects that bridges exercised were very dependent on joint action with the roughness. In real terms, it was verified the dissipation of high quantity in the channel, explaining the process of recorded in historical flood events, such as occurred in the year 2011.